TSH-secreting pituitary adenoma in a patient with paranoid schizophrenia: case report - Valdivieso-Jiménez, Glauco (2025)
The clinical case of a patient with paranoid schizophrenia and persistent anxiety, associated with central hyperthyroidism due to a pituitary microadenoma, is presented. A 24-year-old male with psychotic symptoms and persistent anxiety with somatic symptoms, receiving therapeutic doses of clozapine and benzodiazepines showed clinical improvement after a joint management approach with the endocrinology department due to central hyperthyroidism. Biochemical hormonal analysis and imaging studies were necessary to diagnose a TSH-secreting pituitary microadenoma (thyrotropinoma), a rare medical condition associated in this case with a severe mental disorder. Interdisciplinary management is essential in clinical contexts where diagnostic uncertainty arises, requiring a comprehensive clinical management.